2016
DOI: 10.1038/srep38240
|View full text |Cite
|
Sign up to set email alerts
|

Bordetella pertussis outer membrane vesicle vaccine confers equal efficacy in mice with milder inflammatory responses compared to a whole-cell vaccine

Abstract: The demand for improved pertussis vaccines is urgent due to the resurgence of whooping cough. A deeper understanding of the mode of action of pertussis vaccines is required to achieve this improvement. The vaccine-induced effects of a candidate outer membrane vesicle vaccine (omvPV) and a classical protective but reactogenic whole cell vaccine (wPV) were comprehensively compared in mice. The comparison revealed essential qualitative and quantitative differences with respect to immunogenicity and adverse effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 61 publications
1
48
1
Order By: Relevance
“…8 Subcutaneous immunization of outer membrane vesicle pertussis vaccine (omvPV) could be an improved alternative, as it elicits high serum IgG levels against a broad antigen range 10 and a mixed Th1, Th17, and Th2 response. 11 This response is comparable to the response induced by a B. pertussis infection, but importantly lacks the mucosal immune responses. 8,[12][13][14] Vaccine administration directly into the respiratory tract provides better protection, compared with intramuscular administration, because of its induction of local immune responses.…”
Section: Introductionmentioning
confidence: 79%
“…8 Subcutaneous immunization of outer membrane vesicle pertussis vaccine (omvPV) could be an improved alternative, as it elicits high serum IgG levels against a broad antigen range 10 and a mixed Th1, Th17, and Th2 response. 11 This response is comparable to the response induced by a B. pertussis infection, but importantly lacks the mucosal immune responses. 8,[12][13][14] Vaccine administration directly into the respiratory tract provides better protection, compared with intramuscular administration, because of its induction of local immune responses.…”
Section: Introductionmentioning
confidence: 79%
“…First, lessons were learnt from broadly studied differences between the efficacy of wPV and aPV and between vaccines and natural infections. In this regard, omvPV were found to induce broad antibody responses and a mixed Th1/Th17-dominated T cell response in mice, resembling responses induced by wPV 21 and infection. 45 However, though responses to infection often serve as a reference, we know from past studies that natural infections confer improved protection compared to current vaccines, but do not promote life-long immunity to Bp.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies with omvPVs have shown that they confer protection in mice after both subcutaneous and mucosal immunization with a mixed Th1/Th17 response, similar to the response induced by infection. [19][20][21] These results suggest that omvPVs have the potential to be a safe and effective next-generation pertussis vaccine.…”
Section: Introductionmentioning
confidence: 85%
“…and characterizing the immune response as well as protective immunity (285)(286)(287)(288)(289)(290)(291)(292)(293)(294)(295). In animal studies, immunization with outer membrane vesicles led to not only better humoral and cellular (Th17) memory, but also to a significant increase in IgA titers, which is one of the major hurdles of current vaccination strategies against this pathogen (296)(297)(298). It is important to highlight that the increase in IgA responses upon immunization with outer membrane vesicles is only obtained when these are administrated mucosally (299).…”
Section: Novel Vaccination Strategiesmentioning
confidence: 99%